Characteristics and Dynamics of Sunni Sufism at the As'adiyah Sengkang Wajo Islamic Boarding School - Giling, Mustamin; Tahir, Muhyiddin; Alhadar, Muhdi; Arifin, Zainuddin; Ulama'i, Khaerul Asy'ari (Jurnal Ushuluddin, 2025)
This study examines the historical development and contemporary practices of Sufism at the As'adiyah Sengkang Islamic Boarding School in Wajo, South Sulawesi, from the early 20th century to the present. Using a descriptive qualitative approach, data were collected through observation, interviews with the boarding school's leadership, teaching staff, alumni, and students, as well as a review of the institution's historical documents. The findings indicate that As'adiyah practices a form of Sunni Sufism, reflected in the tradition of halaqah-based learning, the use of yellow books, and the development of moderate religious attitudes. This Sufi orientation significantly shapes the students' personal ethics—manifested in humility, respect for teachers (barakka'na Gurutta'), and ritual discipline—and contributes to the creation of social harmony in the surrounding community. Theoretically, this study contributes to the field of local Sufism by demonstrating that the internalization of Sunni Sufism in the Islamic boarding school education system functions not only as a spiritual discipline but also as a socio-cultural mechanism that fosters religious moderation and social resilience within the Muslim community. These findings confirm the role of Sufism as a transformative force in Islamic education and as a foundational element for strengthening religious moderation in contemporary Indonesia